Use of Midodrine for Intraoperative Hemostasis in Cutaneous and Percutaneous Surgery - Joanna Dong; Naiem T. Issa; Michael Kaiser; Simonetta I. Gaumond; Michael Solis; Joel Gil; Robert S. Kirsner; Stephen C. Davis; Joaquin J. Jimenez (JID Innovations)
Owing to the increasingly high volume of cutaneous and percutaneous procedures performed annually, the demand for local anesthesia has steadily risen. The gold-standard formulations for local anesthesia contain epinephrine at a concentration of 1:100,000 added to lidocaine to aid in hemostasis. Epinephrine, an α-agonist, also exhibits off-target β-adrenergic effects that carry risk of adverse events with these injections. Furthermore, the ongoing global shortage of epinephrine highlights the need for a safer and viable alternative. Midodrine, a targeted a1-adrenergic receptor agonist, is utilized as a vasopressor to induce arterial and venous vasoconstriction. We developed a formulation of 2% lidocaine combined with 1:2,000,000 epinephrine and 50 μM midodrine (midodrine/lidocaine/epinephrine formulation), hypothesizing that this combination would exhibit synergism on hemostasis. In a porcine model of blood loss after punch biopsies, our formulation was compared with 2% lidocaine; 2% lidocaine with 1:100,000 epinephrine; 2% lidocaine with 1:2,000,000 epinephrine; and 2% lidocaine with 50 μM midodrine. Our results indicate that 2% lidocaine with 1:100,000 epinephrine and our midodrine/lidocaine/epinephrine formulation were statistically comparable, with both significantly reducing bleeding when compared with the 2% lidocaine (P < .05). The 2% lidocaine with midodrine alone also showed additional promise as an effective hemostatic formulation. Thus, combination of low-concentration epinephrine and midodrine with lidocaine may exhibit synergistic hemostatic effect in cutaneous surgical settings while reducing potential off-target effects of either vasoconstrictor alone at higher concentrations as adjunct monotherapies.